Facilitation and competition in the high Arctic: the importance of the experimental approach - Dormann, Carsten; Brooker, R.W. (Acta Oecologica, 2002)
In the last decade, plant ecologists have focussed more on the occurrence of positive plant-plant interactions than ever before. Especially in severe environments, such as the Arctic, species removal experiments tend to find facilitative rather than competitive effects, casting doubt on the importance of competition under extreme growing conditions. Two approaches to measure plant-plant interactions presented here reveal that competition affects plant growth even in the high Arctic. Luzula confusa and Salix polaris show a reduced growth in mixed stands compared with pure. This competition effect is not detected in a removal experiment, which inevitably also alters site microclimate. Indeed, in the latter experiment, facilitative effects of Luzula on Salix were found. Evidently, both facilitation and competition are acting and important. Causes and implications are discussed using a conceptual model derived from that of Brooker and Callaghan (1998).